Mechanisms for reducing/eliminating chronic neuropathic pain with a focus on platelet-rich plasma - Damien P. Kuffler; Christian A. Foy (Experimental Biology and Medicine)
Peripheral nerve trauma commonly results in chronic neuropathic pain by up-regulating the synthesis and release of pro-inflammatory mediators from local and invading cells and inducing hyperexcitability of nociceptive neurons and spontaneous electrical activity. The pain decreases when these cells down-regulate genes supporting the pro-inflammatory state, up-regulate genes for expressing anti-inflammatory factors, and modulate genes that reduce nociceptive neuron spontaneous electrical activity. Pharmacological agents, the primary technique for reducing pain, do not eliminate pain, and <50% of patients achieve benefits because they do not address the underlying causes of pain. Alternative techniques providing longer lasting, but not complete or long-term pain relief include surgical interventions, electrical stimulation, and antibody treatment. Anti-inflammatory mediators can reduce pain, but the effect is not complete or long-lasting. Platelet-rich plasma (PRP) contains a readably available evolutionarily developed cocktail of factors that induce longer-lasting and more significant, but not complete, pain relief than other techniques. However, a novel study shows that unique formulations of PRP can induce long-term pain elimination. This review examines (1) the efficacy of drugs, regenerative peripheral nerve interface (RPNI), targeted muscle reinnervation (TMR), and PRP in reducing chronic neuropathic pain, (2) recent clinical data showing that a novel PRP application technique induces long-term chronic neuropathic pain reduction/elimination, and (3) discusses why the novel PRP may be more effective in reducing/eliminating chronic neuropathic pain.